2010
DOI: 10.3174/ajnr.a2153
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Artery Complications Associated with the Mynx Closure Device

Abstract: BACKGROUND AND PURPOSE:Devices to close a femoral arteriotomy are frequently used after catheterization for interventional radiology and cardiac procedures to decrease the time to hemostasis and ambulation and, potentially, to decrease local complications. The Mynx vascular closure device uses a sealant designed to occlude the access tract, resulting in hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…Closure with the Mynx device leads to enhanced patient comfort, rapid haemostasis, reduced time to ambulation, and hospital stay [8,9]. Published results with Mynx are variable with some studies reporting it is safe and effective and others reporting less favourable complication rates mainly in the early stages of deployment and especially associated with a new operator's learning curve [7][8][9][10]. Our study found that the Mynx was indeed an effective closure device (98.9% successful deployment).…”
Section: Discussionmentioning
confidence: 57%
“…Closure with the Mynx device leads to enhanced patient comfort, rapid haemostasis, reduced time to ambulation, and hospital stay [8,9]. Published results with Mynx are variable with some studies reporting it is safe and effective and others reporting less favourable complication rates mainly in the early stages of deployment and especially associated with a new operator's learning curve [7][8][9][10]. Our study found that the Mynx was indeed an effective closure device (98.9% successful deployment).…”
Section: Discussionmentioning
confidence: 57%
“…A recent review by Fields et al 47 underscores this concept, as the authors found that among patients with follow-up femoral angiographic studies after having undergone previous arteriotomy closure with the Mynx device, 18% had intravascular sealant and 11% had pseudoaneuryms. With the exception of one patient, all were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fields and colleagues observed an 18% incidence of intravascular Mynx sealant and 11% rate of pseudoaneurysm formation among 26 patients who underwent follow-up femoral artery angiography at a mean time point of 6 days following initial arterial closure 2. One patient with intravascular sealant underwent surgical exploration for near occlusion of the ipsilateral superficial femoral artery.…”
Section: Discussionmentioning
confidence: 99%